Sei sulla pagina 1di 7

SOLUTION SET VII FOR 18.075–FALL 2004

4.

Series Solutions of Differential Equations:Special Functions

4.10. Differential Equations Satisfied by Bessel

46. Obtain the general solution of each of the following equation in terms of Bessel functions or, if possible, in terms of elementary functions:

(a) xy 3y + xy = 0,

(b)

(c)

(d) xy + (2x + 1)(y

(e) xy y

(f)

(g)

(h)

(i) xy + (1 + 4x 2 )y

x 4 y + a 2 y = 0, y x 2 y = 0, xy + (1 + 2x)y

xy y + 4x 3 y = 0,

1

x 2 y + xy (x 2 + 4 )y = 0,

+ y) = 0,

xy = 0,

+ y = 0.

+ x(5 + 4x 2 )y = 0.

Solution. (a) Rewrite the equation as:

x

2

y

��

3xy + x 2 y = 0.

Following the method described in section 4.10 and in class (in coming Friday!), let A =

2, B = 0, C = 1, s = 1, p = 2.Then,letting Y following differential equation:

XY (X) + XY (X) + (X 2 4)Y (X) = 0

hence Y = Z 2 (X). Therefore, the general solution of the equation in (a) is given by:

satisfies the

= y/x 2 , X

= x we get

that Y

y =

2

x (c 1 Y 2 (x) + c 2 J 2 (x)).

(b) Rewrite the equation as:

x

2

y

��

xy + 4x 4 y = 0.

Following the method described in section 4.10 and in class, let A = 1, B = 0, C = 1, s = 2, p = 1/2. Then,letting Y = y/x, X = x 2 we get that Y satisfies the following differential equation:

hence Y = Z

XY (X) + XY (X) + (X 2 1/4)Y (X) =

0

1 (X).Therefore, the general solution of the equation in (b) is given by:
2

y = x(c 1 J

1

2

(x

2

) + c 2 J

1

2

(x

2

)) = C 1 cos x

2

+ C 2 sin x

2

.

Date: November 7, 2002.

1

2

SOLUTION SET VII FOR 18.075–FALL 2004

I

1

2

(c)

(x)

By setting X = ix, the general solution is found to be y = c 1 I 1 2 (x) + c 2 I 1 2 (x). Since

=

2

�x

2

�x

sinh x, and I

1

2

(x) =

cosh x, the general solution reads

y =

2

�x

(c 1 sinh x + c 2 cosh x).

(d) Rewrite the equation as

2

x y

��

+ x(2x + 1)y + (2x 2 + x)y

=

0.

= 1, s =

1, p = 0. Then, letting Y = ye x , X = x, we get that Y satisfies the following differential equation:

Following the method described in 4.10 and in class, let A = 0, B = C

=

1, r

X 2 Y (X) + XY (X) + X 2 Y (X) = 0,

hence

Y

=

Z 0 (X) Y

=

c 1 J 0 (X) + c 2 Y 0 (X).

Therefore, the general solution of (d) is

y

(e) Rewrite the equation as

=

e

x

(c 1 J 0 (x) +

x

2

y

��

xy

x

2

y

c 2 Y 0 (x)).

=

0.

Similar to (d), one can see that if we let [A = 1, B = 0, r = 0, C = i, p = 1 and s = 1]

Y =

y

,

x

and X = ix,

then X, Y satisfy X 2 Y (X) + XY (X) + (X 2 1)Y (X) = 0. So Y = Z 1 (X), and, hence, the general solution is

= x(c 1 I 1 (x) + c 2 K 1 (x)).

y

=

xZ 1 (ix) y

(f) Rewrite the equation as

x

2

y

��

+

a 2

2 y

x

=

0.

1

Similar to (d), one can see that if we let [A = 2 , B = 0, r = 0, C = a, p =

Y

= y x

,

and X =

a

,

x

then X, Y satisfy

1

X 2 Y ”(X) + XY (X) + (X 2 4 )Y (X) =

So Y = Z 1 (X), and, hence, the general solution is

2

y =

a
a

xZ 1 (

2

x

) y

=

x(c 1 sin (

a

x

) + c 2 cos (

(g) Rewrite the equation as

x

2 ��

y

x

4

y

=

0.

0.

a

x

)).

1

2

and s = 1]

SOLUTION SET VII FOR 18.075–FALL 2004

3

Similar to (d), one can see that if we let [A = f rac12, B = 0, r = 0, C

then X, Y satisfy

Y

= y

x

,

and X =

ix

2

2

,

1

X 2 Y (X) + XY (X) + (X 2 16 )Y (X) =

0.

=

i

2

, p =

1

4

and s = 2]

So Y

= Z

1

(X), and, hence, the general solution is

 

4

y

=

i

xZ ( 1 4 2
xZ
(
1
4
2

x

(h) Rewrite the equation as

x 2 y

2 ) y

=

x(c

1 I

x 2

1
1

4

2

(

��

+ x(1 + 2x)y + xy

=

) + c

0.

2 I

x 2

1
1

4

2

(

)).

Similar to (d), one can see that

if we let [A = 0, B = 1, r = 1, C = i, p = 0 and s = 1]

Y = ye x ,

and X = ix,

then X, Y satisfy

X 2 Y (X) + XY (X) + X 2 Y (X) = 0. So Y = Z 0 (X), and, hence, the general solution is

y = e x Z 0 (ix) y = e x (c 1 I 0 (x) + c 2 K 0 (x)).

(i) Rewrite the equation as

x

2

y

��

+ x(1 + 4x

2

)y

+ x

2

(5 + 4x

2

)y = 0.

We

notice that if we let [A = 0, B = 1, r = 2, C = 1, p = 0 and s = 1]

Y = e x

2

y,

X = x,

the differential equation becomes

X 2 Y (X) + XY (X) + X 2 Y (X) = 0,

which has solution Y (X) = Z 0 (X). Hence, the general solution to the given equation is

y(x) = e

x

2

Z 0 (x) y(x) = e

x

2

(c 1 J 0 (x) + c 2 Y 0 (x)).

47. The following two equations each have arisen in several physical investigations. Express the general solution of each equation in terms of Bessel functions and also show that it can be expressed in terms of elementary functions when m is an integer:

(a)

(b)

y

y

��

��

2

y =

m(m+1)

2m

x

y

y, y = 0.

x

2

2

Solution. (a) Rewrite the equation as

x 2 y (2 x 2 + m(m + 1))y = 0.

Use the method we used in problem 46, we get that, if we set [A =

i�, p = m + 1

2

and s = 1]

2 1 , B = 0, r = 0, C

=

4

SOLUTION SET VII FOR 18.075–FALL 2004

then

So Y

= Z

m+

Y =

y x , and X = i�x,

X 2 Y (X) + XY (X) + (X 2 (m +

1 (X), and the general solution is
2

1

2

) 2 )Y (X)

=

0.

y

=

xZ

m+

1

2

(i�x)

=

x(c 1 I x(c 1 I

m+

m+

1

2

1

2

(�x) + c

(�x) +

2

I

(m+

c 2 K

m+

1

2

1 ) (�x))

2

(�x))

if m +

2 1 is not an integer,

if m +

2 1 is an integer.

Since I

m+

1

2

can be expressed by elementary functions when m is an integer, it’s clear that

the general solution can also be expressed by elementary functions when m is an integer. (b) Rewrite the equation as

x 2 y 2mxy 2 x 2 y

=

0.

Use the method we used in problem 46 and in class, we get that, if we set [A = m + 2 , B =

0, r = 0, C = i�, p = m +

1

1

2

and s = 1]

Y =

y

, 1 m+ x 2
,
1
m+
x
2

and X = i�x,

then

So Y

= Z

m+

y(x)

X 2 Y (X) + XY (X) + (X 2 (m +

1

2

(X), and the general solution is y(x) = x

=

x

x m+ 2 (c 1 I

(c 1 I

m+

2

1

1

m+

m+

1

2

1

2

(�x) + c

(�x) + c 2 K

2

I

(m+

m+

1

2

1

2

) (�x))

(�x))

1

2

) 2 )Y (X)

m+

1

2

Z

m+

1

2

=

0.

(i�x), which is

if

m +

2 1 is not an integer,

if

m +

2 1 is an integer.

Since I

m+

1

2

can be expressed by elementary functions when m is an integer, it’s clear that

the general solution can also be expressed by elementary functions when m is an integer.

48. Show that for the differential equations

xy + 3y + 4xy

=

0

the condition y(0) = 1 determines a unique solution, and hence that y (0) can not also be prescribed. Determine this solution.

Solution. Rewrite the equation as

x

Similar to problem 46, one can see that if we let [A = 1, B = 0, r = 1, C = 2, p = 1, r = 0 and s = 1]

2

y + 3xy + 4x 2 y

=

0.

Y = xy,

and X = 2x,

then X, Y satisfy

X 2 Y ”(X) + XY (X) + (X 2 1)Y (X) = 0.

SOLUTION SET VII FOR 18.075–FALL 2004

5

So Y = Z 1 (X), and, hence, the general solution is

y = x 1 Z 1 (2x)

=

According to the relations (as x 0)

2

p

p (x) �(1 + p)

J

x p ,

x

1

Y

p

(c 1 J 1 (2x) + c 2 Y 1 (2x)).

(x) � −

2 p (p 1)!

x

p

,

where p = 1, it’s easy to see that y(0) = 1 implies c 1 = 1 and c 2 = 0 since the second term blows up at x = 0! So the condition y(0) = 1 determines a unique solution, which is

y = x 1 J 1 (2x).

49. Find the most general solution of the equation

for which

where P is a given constant.

x

2 ��

y

+ xy

+ (x 2 1)y = 0

lim 2�xy(x) = P

x0

Solution. This equation is the Bessel equation with p = 1. Clearly,

y(x) = C 1 J 1 (x) + C 2 Y 1 (x)

is the general solution of the above equation. deduce that:

From the behavior of J 1 (x) as x 0, we

lim 2�xJ 1 (x) = 0

x0

therefore the condition in the exercise is reduced to

From the behavior (as x 0)

we get that:

lim 2�xY 1 (x) = P.

x0

Y p (x) 2 p (p 1)!

x p

lim xY 1 (x) = 2/�.

x0

Hence the required limit condition implies

C 2 = P/4.

Thus the most general solution of

for which

is :

x

2 ��

y

+ xy

+ (x 2 1)y = 0

lim 2�xy(x) = P

x0

y(x) = C 1 J 1 (x)

P

4

Y 1 (x).

6

SOLUTION SET VII FOR 18.075–FALL 2004

50. The differential equation for small deflections of a rotating string is of the form

d

dx

(T

dy

dx

) + ω� 2 y

) + ω� 2 y

=

0.

Obtain the general solution of this equation under the following assumptions:

(a)

(b)

(c)

T = T 0 x

T = T 0 x n , ω = ω 0 , n = 2; T 0 = l 2 ω 0 2 .

n

, ω = ω

0

x

n

; T 0 = l 2 ω 0 2 .

T = T 0 x 2 , ω = ω 0 ; T 0 = 4ω 0 2 .

Solution. (a) Rewrite the equation as

x

2

��

y + nxy

+

x

2

l 2 y

=

0.

By the method used in problem 46, we get that, if we set [A =

1

l

, p =

n1

2

and s = 1]

n1 , B = 0, r = 0, C =

2

then

Y = x

n1

2

y,

and X =

x

l ,

X 2 Y (X) + XY (X) + (X 2 ( n 1 ) 2 )Y (X)

2

So Y = Z n1 (X), and, hence, the general solution is

2

y

1n

x

= x 2

Z n1 (

2

l

).

=

0.

(b) Rewrite the equation as

x 2 y

��

1

+ nxy + l 2 x n2 y

=

0.

By the method used in problem 46, we get that, if we set [A = n1 , B = 0, r = 0, C =

2

(n1) 2

l(2n) , p = (n2) 2

2

and s = 2n ]

2

then

Y

= x

n1 2

2

y,

and X =

2n

l(2 n)

x

2

,

X 2 Y (X) + XY (X) + (X 2 (

n

1

n

2

) 2 )Y (X)

So Y = Z n1 (X), and, hence, the general solution is

n2

=

0.

y

1−n 2 2−n x 2 Z n−1 ( n−2 l(2 − n)
1−n
2 2−n
x 2
Z n−1 (
n−2
l(2 − n)

= x 2

),

n = 2.

(c)

Rewrite the equation as d

dx

(4x 2 y (x)) + y

=

0 x

2

y + 2xy

+

1

4

y = 0.

Let Y = xy, then the equation above becomes [A = 2 , B = 0, r = 0,and s = 0]

1

Y (X) +

1

x

Y (X)

=

0.

SOLUTION SET VII FOR 18.075–FALL 2004

7

So Y (X) = cx 1 , and Y

=

Y (X)dx = c 1 log x + c 2 . Then the general solution is

y

=

x

1

2 (c 1 log x + c 2 ).